Aromatherapy improves nausea, pain, and mood for patients receiving pediatric palliative care symptom-based consults: A pilot design trial. Issue 2 (April 2020) - Weaver, Meaghann S.; Robinson, Jacob; Wichman, Christopher
Abstract: Objective: The role of aromatherapy in supportive symptom management for pediatric patients receiving palliative care has been underexplored. This pilot study aimed to measure the impact of aromatherapy using validated child-reported nausea, pain, and mood scales 5 minutes and 60 minutes after aromatherapy exposure. Methods: The 3 intervention arms included use of a symptom-specific aromatherapy sachet scent involving deep breathing. The parallel default control arm (for those children with medical exclusion criteria to aromatherapy) included use of a visual imagery picture envelope and deep breathing. Symptom burden was sequentially assessed at 5 and 60 minutes using the Baxter Retching Faces scale for nausea, the Wong-Baker FACES scale for pain, and the Children's Anxiety and Pain Scale (CAPS) for anxious mood. Ninety children or adolescents (mean age 9.4 years) at a free-standing children's hospital in the United States were included in each arm (total n = 180). Results: At 5 minutes, there was a mean improvement of 3/10 (standard deviation [SD] 2.21) on the nausea scale; 2.6/10 (SD 1.83) on the pain scale; and 1.6/5 (SD 0.93) on the mood scale for the aromatherapy cohort ( p < 0.0001). Symptom burden remained improved at 60 minutes post-intervention (<0.0001). Visual imagery with deep breathing improved self-reports of symptoms but was not as consistently sustained at 60 minutes. Significance of results: Aromatherapy represents an implementable supportive care intervention for pediatric patients receiving palliative care consults for symptom burden. The high number of children disqualified from the aromatherapy arm because of pulmonary or allergy indications warrants further attention to outcomes for additional breathing-based integrative modalities.